Understanding risk factor influenced food security faced by elderly during flood disaster in Bera, Pahang, Malaysia / Hamidah Hamzah - Hamzah, Hamidah (2016)
Flood disaster can be considered as emergencies situation where food security can be one of the topic that can be looked up. Food security can be defined when the food is available, can be access, and acquired in acceptable means at any given time that possibly will maintain health and wellbeing, while food insecurity gives contrasting meaning to it where limited or uncertain ability to attain nutritious food in socially acceptable means. The main aim of this study was to identify the risks factor that influenced food security faced by elderly during flood disaster at Sungai Pahang basins area. The determination of coping strategies of the victims of the flood disaster also identified in this research paper. This study enlighten a qualitative approach for the data collection which engaging semi structured interview between eight selected individual affected by the flood disaster and thematic analysis is using to analyze the themes for each of the objectives. The qualitative data indicated that inappropriate food assistance, feeling insecurity and mental and emotional stress were the major risk factor of food security for the elderly that can be identified during the flood disaster .As from the identification of the risk factor it can be conclude that it is very important to be specifically and directly focus to the needs, pay more attention, and understand the situation of the elderly as they are tend to be a vulnerable group to food insecurity especially in emergencies situation.